2014
DOI: 10.1016/j.bbabio.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of cardiolipin in mitochondrial bioenergetics

Abstract: Cardiolipin is a unique phospholipid which is almost exclusively located in the inner mitochondrial membrane where it is biosynthesized. Considerable progress has recently been made in understanding the role of cardiolipin in mitochondrial function and bioenergetics. This phospholipid is associated with membranes designed to generate an electrochemical gradient that is used to produce ATP, such as bacterial plasma membranes and inner mitochondrial membrane. This ubiquitous and intimate association between card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
358
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(371 citation statements)
references
References 129 publications
5
358
0
2
Order By: Relevance
“…129,130 Besides phosphatidylinositols, levels of the mitochondrial glycerophospholipid, cardiolipin, are also tightly controlled. Cardiolipin is abundant in the inner mitochondrial membrane where it acts as a key component of the electron transport chain, as well as having an essential role in the initiation of apoptosis through association with cytochrome C. 131 To coordinate these essential mitochondrial processes, cardiolipin synthase as well as a range of phospholipases exquisitely maintain cardiolipin levels within the mitochondria. 132 Another key mechanism in regulating the availability of phospholipids at different locations, particularly on which surface of the phospholipid bilayer, is mediated by nonspecific and specific lipid transporters.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…129,130 Besides phosphatidylinositols, levels of the mitochondrial glycerophospholipid, cardiolipin, are also tightly controlled. Cardiolipin is abundant in the inner mitochondrial membrane where it acts as a key component of the electron transport chain, as well as having an essential role in the initiation of apoptosis through association with cytochrome C. 131 To coordinate these essential mitochondrial processes, cardiolipin synthase as well as a range of phospholipases exquisitely maintain cardiolipin levels within the mitochondria. 132 Another key mechanism in regulating the availability of phospholipids at different locations, particularly on which surface of the phospholipid bilayer, is mediated by nonspecific and specific lipid transporters.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…rely on glycolytic metabolism to a greater extent than unaffected, age-matched controls, likely due to an impairment in fat oxidation. These findings highlight the crucial role that mitochondrial CL plays in skeletal muscle oxidative metabolism and mitochondria bioenergetics processes [26].…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…Actually, this specific phospholipid of the mitochondria plays an important role in respiratory chain (biogenesis, stability and activity of the respiratory complexes), in the β-oxidation of fatty acids and is involved in the last step of energy conversion, namely the production of ATP [24][25][26]. Crystallographic and nuclear magnetic resonance studies showed the presence of CL, in…”
Section: Myostatin and Membrane Phospholipids Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…CL is now recognized as a prerequisite for optimal activity of respiratory chain proteins, including complex I (NADH/quinone oxidoreductase), complex III (cytochrome bc 1 ), complex IV (cytochrome c oxidase), and complex V (ATP synthase). A number of possible functions have been proposed for CL in OxPhos, ranging from protein rigidification to proton transfer (8). CL-protein interactions in the inner mitochondrial membrane are not limited to the OxPhos complexes, as witnessed by a rapidly growing list of other proteins interacting specifically with CL, ranging from ADP/ATP carriers to translocases (9,10).…”
mentioning
confidence: 99%